السينوغرافيا في مسرح القرن العشرين وارتباطها بفـُنون التصوير واتجاهاتها - معاد عبد الرزاق; وزيت حسام دبس (Latakia University Journal -Engineering Sciences Series, 2019)
إنَّ تطور فنون المسرح عبر العصور المُختلفة من رقص وتمثيل وموسيقى وسينوغرافيا ... أسهم في بلورة الخصائص التشكيلية والتعبيرية التي تتخذها كل من تلك الفنون في صياغة الصورة الجمالية للعرض المسرحي . وقد كان لفنون التصوير الدور الرئيس، ويكاد يكون الأساس، في تطور مفهوم السينوغرافيا ، وما كان للحركات الفكرية والنظريات الفلسفية في الفن والأدب على حدٍّ سواء من أثر ٍ في فنون التصوير واتجاهاتها من جهةٍ، وفي الحُضور التشكيلي لتلك الفنون في سينوغرافيا مسرح القرن العشرين من جهة ٍ أخرى . يُقدّم البحث تعريفا ً للسينوغرافيا ، ومن ثم يُناقش القيم الجمالية لفنِّ المسرح والبُعد التشكيلي للمناظر المسرحية، والأساليب والتقنيات التي ترتبط بها. إلى جانب عرضه لأهمِّ المبادئ التي تستند إليها فنون التصوير واتجاهاتها كأحد الحلول الناجعة في عرض الرُّؤية البصرية التي ينشُدها مُصممو المناظر المسرحية في آليات إبداعهم لسينوغرافيا العرض المسرحي . ويخلـُص البحث إلى عدد ٍ من النـُّقاط التي تـُلقي الضوء على المكانة التي تحتلها فنون التصوير في الفن المسرحي . The development of theatrical arts [dance, music, scenography] over the ages has left a major impact on refining the artistic and expressionistic characteristics of these arts, in creating the aesthetical image of the theatrical performance. Pictorial [Painting] arts have had a significant, and almost sole, role in developing the concept of scenography. Moreover, intellectual movements and philosophical theories in literature and arts have affected pictorial arts and their trends on the one hand, and the presence of such arts in the scenography of the 20th C theatre on the other hand. This research introduces a definition of scenography. Then, it addresses the artistic values of theatre and the artistic dimension of theatrical tableaux; as well as the techniques and methods associated with them. Moreover, it highlights the most important principles of pictorial arts, used in visual arts, along with their tendencies, as one of the appropriate options, in displaying the scenographic vision, conjured up by theatrical tableaux-designers, in creating theatrical scenography. This research concludes with a few points that shed light on the significance of pictorial arts in theatre.